If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4(1 + -3x) = 2x + -1(x + -1) 3x + (1 * -4 + -3x * -4) = 2x + -1(x + -1) 3x + (-4 + 12x) = 2x + -1(x + -1) Reorder the terms: -4 + 3x + 12x = 2x + -1(x + -1) Combine like terms: 3x + 12x = 15x -4 + 15x = 2x + -1(x + -1) Reorder the terms: -4 + 15x = 2x + -1(-1 + x) -4 + 15x = 2x + (-1 * -1 + x * -1) -4 + 15x = 2x + (1 + -1x) Reorder the terms: -4 + 15x = 1 + 2x + -1x Combine like terms: 2x + -1x = 1x -4 + 15x = 1 + 1x Solving -4 + 15x = 1 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 15x + -1x = 1 + 1x + -1x Combine like terms: 15x + -1x = 14x -4 + 14x = 1 + 1x + -1x Combine like terms: 1x + -1x = 0 -4 + 14x = 1 + 0 -4 + 14x = 1 Add '4' to each side of the equation. -4 + 4 + 14x = 1 + 4 Combine like terms: -4 + 4 = 0 0 + 14x = 1 + 4 14x = 1 + 4 Combine like terms: 1 + 4 = 5 14x = 5 Divide each side by '14'. x = 0.3571428571 Simplifying x = 0.3571428571
| 3(x+2)/5=6 | | 4-2(3-2x)=5 | | X+x+x=16 | | 3-5(2x+1)=2x | | 3y^2-9y-84=0 | | 7(2x-1)=-35 | | A(b-2)=c(b+3) | | 6(x+5)=-12 | | 5(x-2)-3(x+1)=0 | | 6x-3=6x+2 | | 100-10x=40 | | x^2-10xy-24y^2=0 | | 9(x-5)-5(x-2)+2x= | | 2y=8-(y-2) | | 5(x+1)=12-x | | 18x+72=21 | | N+7=4 | | 9x+7x=69+x | | 5x-1=3x+115 | | 2x+38=4x+12 | | 12x+30=6x+108 | | X-4(x+3)=2 | | -2(5)+5= | | 35x=25x+1500 | | x=100+1y | | 4x^2-23x+8=-2+3 | | 5x-13+7x+3=180 | | 3(9+4)-7= | | 7x-10y=1 | | 6(x+4)=2(x+24) | | 7*5+xb=25+7x-5b | | 5x-7=58-8x |